Epidemiologia comparativa entre a ferrugem asiática da soja e a ferrugem da folha do trigo - Viero, Virgínia Crestani (2008)
The soybean is one of the most important commodities in the Brazilian agribusiness. Its production, however, has been affected by several diseases, especially the Asian rust which had presented outbreaks in Brazil since 2001. Because the soybean cultivars are susceptible to rust, the control of this disease is largely based on applications of fungicide, either preventively or eradicatively. However, little is known about the rule of latent infections on this disease epidemiology and its control. Another important control issue is the time of plant protection provided by the preventive sprays of fungicides, which may vary among cultivars and active ingredients, but it is necessary to define the control strategies. Such important questions were in several experiments conducted at the Universidade de Passo Fundo in 2006 and 2007. Because Asian rust is a new disease in Brazil, a comparative study was conducted with the wheat leaf rust in order to validate the data and to make the results more easily understood by consultants and growers. All trials were conducted in growth chambers with control of temperature and luminosity and included eight cultivars, four of soybeans (CD 213RR, CD 214RR, CD 219RR, and BRS 154) and four of wheat (BRS Angico, Fundacep Nova Era, Ônix, and Safira). In the curative trials, the plants were first inoculated with the pathogens (Phakopsora pachyrhizi e Puccinia triticina) and then sprayed with a triazol fungicide (tebuconazol) and a mix of triazol + strobylurin (epoxiconazol + pyraclostrobin) at daily intervals. The evaluations included countings of disease lesions and uredia, fungal spores, and spore germination. The wheat leaf rust was controlled up to four days after inoculation by the triazol and five days by the mixture. On soybeans, this period was shorter as one day for the triazol and two days for the mixture. The non-controlled infections resulted in spores for both pathosystems. The mixture of triazol and strobylurin reduced sporulation of Puccinia triticina, which has not been reported before. The low curative control of the latent infections reinforce the importance of managing soybean rust through protective applications of fungicides. This question was evaluated in other three experiments where the plants were sprayed once with the same fungicides and later inoculated with spore suspensions of the respective pathogens, for a period of 20 days. The spray applications provided a 100% protection of 14 (mixture) to 20 days (triazol) on soybeans. All inoculations resulted in lesion formation on wheat, but there were much lesser spores on plants sprayed with the mixture. The performance of the tested fungicides and the period of plant protection varied significantly between the pathosystems and cultivars.